Analysis of The Filter Bubble Phenomenon in The Use of Online Media for Millennial Generation (An Ethnography Virtual Study about The Filter Bubble Phenomenon) - Sri Seti Indriani; Ditha Prasanti; RANGGA SAPTYA MOHAMAD PERMANA (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2020)
This article describes about phenomenon of Filter Bubble for Millennial Generation in online media. Nowadays, we know that people in searching information are likely to be unaware that their search has been chosen. What is most interesting is how people which are aware on how a filter bubble works but seemed to forget when they search on some information. Researchers and critics are worried because these filters isolate people from getting the information on what they want not on what they need. People might not realize that they are led to partial information blindness. This research is acknowledge their awareness on the filter bubble phenomena especially on Y generation who are believed to be a group of people that adapt fast from the analogue era to the digital era. How they search information nowadays, how bubble filters add their self-value on things and how they prevent themselves from being in a bubble. The research was conducted using a qualitative method with an ethnography virtual approach through LINE group of millennial generation. This approach was to gain more information on the virtual culture, and this case the filter bubble phenomena. Results shows that most informants were not aware on the term of ‘Filter Bubble’, but have been assuming it for quite a while. When they were more informed of this term, they realized that they should be more critical on what they read, and being literated is a significant competence in this era. Though, in addition whether or not this filter bubble could construct their identity, some denied that it didn’t have any relevation while others seemed to think that it did give some additional values on it.Keywords: Filter Bubble, Computer-mediated Communication, ethnography virtual, millennials, and self valueABSTRAKPenelitian ini menjelaskan tentang fenomena bubble filter untuk Generasi Milenial di media online. Sekarang ini, orang-orang dalam mencari informasi cenderung tidak menyadari bahwa pencarian mereka telah dipilih. Hal paling menarik adalah bagaimana orang-orang yang menyadari cara kerja bubble filter namun menjadi lupa ketika mereka mencari informasi. Para peneliti dan kritikus khawatir bubble filter ini mengisolasi orang dari mendapatkan informasi tentang apa yang mereka inginkan, bukan tentang apa yang mereka butuhkan. Orang mungkin tidak menyadari bahwa mereka dituntun pada kebutaan informasi parsial. Penelitian ini bertujuan untuk mengetahui kesadaran generasi Y terhadap fenomena bubble filter: cara mereka mencari informasi saat ini, bagaimana bubble filter menambahkan harga diri mereka pada sesuatu, dan bagaimana mereka mencegah diri mereka dari berada dalam bubble. Penelitian ini menggunakan pendekatan kualitatif dan metode etnografi virtual untuk mendapatkan lebih banyak informasi tentang budaya virtual, terutama fenomena bubble filter. Hasil penelitian menunjukkan bahwa sebagian besar informan tidak mengetahui istilah